Bureaucratization in a Changing Society: Administrative Reforms in Late Nineteenth Century Chile - Barria-Traverso, D (Taylor and Francis Inc., 2018)
During the 1880s, a significant number of Chilean administrative services were reformed following the characteristics of the Weberian bureaucracy. From the analysis of two cases of administrative reform (the so-called Prussianization of the Chilean Army and the creation of institutions in the field of public health), this article seeks to understand why bureaucracy gained ground in nineteenth century Chile. Specifically, the article discusses how social conditions led policy makers to choose bureaucracy as a model for administrative organization. Through this analysis, the article aims to contribute to the theoretical discussion on the causes of bureaucratization. © 2017 Taylor & Francis Group, LLC.